Synthesis of Some New Substituted Quinazolin-4-3H-Ones as Potent Anticonvulsant Agents: Synthesis of New Quinazolinones (Biological Sciences - PJSIR, 2009)
A new series of 3-(4-(2-(6,8-dibromo-3-(substituted phenyl)-4-oxo-3,4-dihydroquinazolin-2-yl)methyl) hydrazinyl)thiazol-2-yl)-2-phenylthiazolidin-4-ones were synthesized and their structures were elucidated on the basis of elemental analyses and spectroscopic studies (IR, 1H-NMR). All the synthesized compounds 1-32 were screened for their anticonvulsant activity at a dose of 30 mg/kg. The compound 31 was found to be the most potent compound of this series showing 90% protection against  MES.